2008
DOI: 10.1111/j.1742-7843.2008.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subchronic versus Acute in utero Exposure to Dexmedetomidine on Foetal Developments in Rats

Abstract: Dexmedetomidine is a highly selective and specific α -2 adrenergic agonist with sedative, analgesic and sympathetic activities. This study was undertaken to investigate the effects of in utero exposure of dexmedetomidine on foetal development and postnatal behaviour in the offspring. Pregnant Sprague-Dawley rats were chronically treated with dexmedetomidine (0, 5, 10 and 20 µ g/kg, subcutaneously) daily from gestation day 7 to day 19. Another group of animals received only a single acute dose of dexmedetomidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Previous studies have also shown that intravenous dexmedetomidine has no adverse effect on parturients and neonates, [31][32][33] similar results were also obtained in the present study. The results showed no difference in the Apgar score, heart rate or NACS compared with the control group.…”
Section: )supporting
confidence: 81%
“…Previous studies have also shown that intravenous dexmedetomidine has no adverse effect on parturients and neonates, [31][32][33] similar results were also obtained in the present study. The results showed no difference in the Apgar score, heart rate or NACS compared with the control group.…”
Section: )supporting
confidence: 81%
“…There were many case reports of use of dexmedetomidine in parturients after the proof of its retention in the placenta with negligible effect on the fetus [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…12 A recent report suggested that dexmedetomidine has few significant effects on pregnant rats; intrauterine exposure has been shown to exert no adverse effects on perinatal morphology of pups, their birth weight, crown-rump length, physical growth or postnatal behaviour. 13 Though reassuring, the clinical relevance of these findings in humans remains inconclusive.…”
mentioning
confidence: 93%